The Singularity of the Otherness’s Role in Language Acquisition by Sheltered Children - Fernanda Rabelo de Carvalho Beltrão; Glória Carvalho (Psicologia, 2008)
The interpretative activity of the otherness has an essencial role in language acquisition. Thus, from a interacionism of structuralist basis, this article seeks to discuss the singular role of a specific otherness – the caretaker – in the linguistic evolution of sheltered children. To reach this objective, it was made a longitudinal investigation, for 11 months, in a sheltering institution from FUNDAC/PE, having been the dialogues of three children with their respective responsible caretakers audio recorded. In the analysis of these dialogues, it was selected children’s verbal production which provoked amazement to the caretaker and/or to the researcher and it was also analyzed also how the caretaker answered this kind of verbal production. To highlight the singularity of the otherness/caretaker, were used dialogues between children and their mothers. The reached results suggest that the place of otherness, when taken by a caretaker, presents singularity marks that might be indicated by the manner of the otherness/caretaker relates to the infantile speaking, as, for example, the indifference attitude which, many times, that otherness has towards the children’s uncommon verbal production.